Seasonal rhythm of pediatric dermatoses in Pakistani population: An observational study - Hira Tariq; Abbass, Alina; Javaed, Hira; Batool, Saelah; Cheema, Ashba Nasir; Asad, Faria (Journal of Pakistan Association of Dermatologists, 2024)
Objective Epidemiological surveys to analyse the patterns of dermatoses in pediatric population are very important for adequate health care management and planning. Seasonal variations provide an insight into possible pathogenic mechanisms involved in disease process. The objective of the study is to analyze the effect of seasonal variations in pediatric dermatoses at a tertiary care hospital in Lahore. Â Methods This was an observational study, conducted in the Dermatology outdoor of Services Hospital Lahore. All children of both genders less than 18 years of age were included in this study. The pattern of dermatoses was assessed in four seasons. The data was analyzed using SPSS ver. 20.0 Role of effect modifiers was analyzed using Chi Square test. Â Results 2216 children were managed in OPD. Infestations (32.94%) were the commonest dermatoses, followed by infections (23.82%) and eczemas (18.55%). Most of the cases in all categories of dermatoses were seen during summer season (47.20%) especially infections and infestations, followed by spring (27.03%), autumn (20.13%), and winter (5.64%). The difference of pattern among dermatoses was statistically significant (p value 0.00). Scabies was the most common dermatosis (28.52%) followed by atopic eczema (12.17%) and tinea corporis (3.88%). Â Conclusion Seasons have significant impact on pattern of pediatric dermatoses reflecting an aetiopathogenic role in causation of these diseases. Â